Kobiety z okresu socjalizmu w ujęciu oral history – metodologiczne wyzwania badań interdyscyplinarnych - Wachowiak, Anna (Adult Education Discourses, 2020)
Did women’s promotion in socialism really happen? To answer this question, it is worth looking at what works in this field were created then in sociology. There were few compact monographs and results of empirical work. There is a limited catalog of topics such as: family transformation in the conditions of industrialization and urbanization, professional position of women and the family, processes of secularization of the family, family models in the workers’ milieu, families in People’s Poland, urban family, modern family, woman-home-work and obviously dominant motif of women’s professional work. These studies do not give voice to women themselves. A focused analysis of these quite recent stories of spoken women living in Poland under communism, as well as personal interviews obtained during the implementation of this project, was the main research problem of the project: Regaininh the future by rebuilding the past. Narratives of women living in communism. Methodological dilemmas that resulted from the interdisciplinary nature of the team implementing this project constituted the dominant theme of the presented article. His main conclusion is that the postulate of working in an interdisciplinary team is very timely. At the same time, women’s social history projects can be implemented according to various paradigms that sometimes stand in opposition to each other. The ability to combine them flexibly determines the strength of such projects as well as their results.